PENGARUH UMUR POHON TERHADAP SIFAT DASAR DAN KUALITAS PENGERINGAN KAYU WARU GUNUNG (Hibiscus macrophyllus Roxb.) - Efrida Basri; T.A. Prayitno; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2012)
This study examines wood properties as the indicator of waru gunung wood quality based on age and axialdirectionand their implication on drying quality. Wood samples used in this study collected from three ages, i.e. 8, 12, and16years.Thesamples were arranged in axial direction of the tree stem,namely, bottom, middle, and top portions. The basicproperties of the wood observed i.e. fiber length, specific gravity (SG), and wood shrinkages for each axial portions wereobserved in radial direction from near pith, central and near bark. Fiber length measurements were undergoneusingprocedure practiced at the Centerfor Research and Development on Forestry Engineering and Forest ProductsProcessingBogor. Specific gravity and shrinkage were determined in accordance with the modified ASTM D143-94, meanwhiledrying properties and qualitieswere observed using the modified Terazawa method.Results revealed that thefiber length and SG of waru gunung were affected by tree ages, andposition of the tree stemin both axialand radial directions. Considering basic propertiesand dryingqualities of the series wood aging, itturned out that wood with tree age of 16 years could comply with the requirementsforfurniture material.